OPTIMIZATION OF WEIGHT ON BIT DURING DRILLING OPERATION BASED ON RATE OF PENETRATION MODEL - Sonny Irawan; Irwan Anwar (Jurnal APTEK, 2012)
Drilling optimization is very important during drilling operation. Optimization of drilling could save time and cost of operation and increases the profit. Drilling optimization aims to optimize controllable variables during drilling operation such as weight on bit (WOB) and bit rotation speed for obtaining maximum drilling rate (ROP). In this study, Bourgoyne and Young ROP model had selected to measure the effects of several parameters during drilling operation. Parameters such as depth, pore pressure, equivalent circulating density, bit weight, rotary speed, bit tooth wear, and jet impact force were extracted from actual drilling report. The penetration model for the field is constructed using the results from statistical method. The result from analysis was used to determine optimum values of weight on bit that give optimum drilling operation. Overall, this study provides complete mathematical model for rate of penetration that was constructed by Bourgoyne and Young. From the study the constants that represented several drilling variables had been determined. The rate of penetration for the field had been predicted based on constants for every data depth. Finally, optimized weight on bit had been calculated for several data points and the results had been simulated and proved using drilling simulator.